Peran Koherensi terhadap Kelentingan Keluarga yang Memiliki Anak dengan Spektrum Autistik (ASA) - Fachrun Naja Maulidia; Melok Roro Kinanthi; Nurindah Fitria; Atari Suci Permata (Jurnal Ilmu Keluarga dan Konsumen, 2018)
Families of children with autism spectrum disorder experience a number of challenges in life, both physically, psychologically and socially. Families who can adapt effectively will be functioning well and prosper. They are not only survived, but also able to gain some positive benefits from the difficult situations. The purpose of this study was to analyze the role of family sense of coherence on family resilience among Families of children with autism spectrum disorder, based on mother's perspective as the primary caregiver. This study also wants to identify the difference of family sense of coherence and family resilience level based on several demographic factors such as the number of children, the age of Autistic children, the age of participant (mother), the amount of family expenditure, level of education, and length of diagnosis. Using quantitative approach with associative design, subjects in this research are 148 mothers who have a child with autism, living in Jabodetabek area. Data were obtained through questionnaire-based research instruments, which is Walsh Family Resilience Questionnaire and The Family Sense of Coherence Scale. The questionnaires were distributed to research participants through foundation or school concerned in autistic children. The data have been obtained and then analyzed by simple regression analysis. The result indicated that family sense of coherence has a positive and significant correlation between family resilience. It is indicated that family sense of coherence can help us to understand how a family becomes resilient when facing a difficult situation.